Personality Prediction through Curriculum Vitae Analysis Involving Password Encryption and Prediction Analysis - Shruti Maheshwari, Gagandeep Kaur (International Journal of Advanced Science and Technology, 2019)
A recruitment process requires an eligibility check, an aptitude evaluation and a psychometric analysis of prospective candidates. The work puts forward an application where the system allows employers to post new job offerings and registered candidates can apply. The application estimates applicant’s emotional aptitude through a psychometric analysis based on a test whereas the professional standard is verified via technical aptitude test. OCEAN Model is used to assess emotional quotient and predict the personality traits. Machine learning techniques such as Logistic Regression are used for modelling the personality predictor. The details of the candidates are kept secure by using a password encryption algorithm. The passwords are only known to the required individuals. The system outputs whether the candidate has been selected for the interview process via dashboard and SMS alerts. A list of candidates is generated for the employer in order to keep track of the shortlisted candidates along with their scores.